Assumptions for inventory modelling: insights from practice. (29th March 2019) - Lättilä, Lauri; Kortelainen, Samuli; Hilletofth, Per
Many types of models have been developed to analyse multi-echelon supply chains. These models tend to rely on certain assumptions which might be too restrictive to be used in practical applications. In this paper we present a decision support system developed for a manufacturing company to aid decision making in both manufacturing and distribution strategy. The model is based on the assumptions of the decision-makers instead of relying on a pre-existing model architecture, which guarantees that the assumptions made are not too restrictive for practical use. The decision support system is based on agent-based modelling. The model was done in close co-operation with the personnel from the case company, and emphasis was based on how the company can use the model in decision making without requiring any special expertise in developing the supply chain alternatives. By using agent-based modelling we were able to take the central assumptions into account and create a decision support system, which the supply chain manager can use to evaluate various supply chain alternatives.